Factors Affecting the Independence of Hospital Management in Iran University of Medical Science - Faridfar, Niloufar (2020)
Introduction: Governmental hospitals have so far managed in different ways to increase the efficiency of hospitals, each of which has its disadvantages and advantages. This study aimed to determine the factors affecting the independence of hospital management in Iran University of Medical Science. Material and Methods: This descriptive-survey study was conducted pragmatically at hospitals of Iran University of Medical Sciences to identify obstacles and provide the necessary infrastructure by conducting study and follow-up. The sample was 94 people including university dean, deputies and chief executives of hospitals, educational and research deputies, therapists and professionals. Questionnaire was used as data collection tools and field data collection method. Results: The mean age of participants was 47.24 ± 5.41 years. Cronbach's alpha of 41 questions was assessed to test the reliability of the questionnaire. The total alpha coefficient was 0.843. The results showed that the mean score of all domains based on experience time was not significantly different (p> 0.05). The mean score of all domains in the first and third items based on education was statistically significant (p <0.05). In other items, there was no significant difference based on education level (p> 0.05). Conclusion: In general, according to the results and extracted five items, the independence of hospital management can improve the efficacy of services and satisfy the patients and staff.